Dyskurs edukacyjny w ujęciu procesualno-kognitywnym - Rypel, Agnieszka (Kultura-Społeczeństwo-Edukacja, 2019)
The paper attempts at presenting diversity in discourse research and defining educational discourse in its new cognitive-procesual aspect. The analysis is concentrated on formalized educational discourse undergoing ideological influences through mass, public and government supervised education. For the detailed discussion multiperspective method including critical and rhetorical analysis has been proposed acknowledging the separateness of makro and discursive strategies together with their topoi in the common ideological – cognitive mean.